Capitalist Practices in Lampung Tobacco Plantations during the Liberal Economy Period - Ajeng Diah Kinanti; Roro Wilis; Ririn Darini (Universitas Hamzanwadi, 2026)
This research aims to examine the practice of capitalism in the production system and labor relations in Lampung tobacco plantations during the liberal economy period. This research uses a historical method. The results show that tobacco plantations in Lampung flourished during the liberal economy period. The government opened opportunities for the private sector to invest in Lampung tobacco plantations. This is evidenced by the trials conducted on the cultivation of Deli and Manila tobacco varieties. The production system and labor relations in Lampung's tobacco plantations during the liberal economy period reflect the existence of capitalist practices. A capitalist class emerged, consisting of private companies, and a working class from the local community. The production system was controlled by private companies, which controlled all means of production and profits. Farmers obtained capital loans, tobacco seeds, fertilizers, and guidance. Then, the tobacco harvest would be purchased by companies with an advance payment system, creating a pattern that benefited companies and harmed farmers because they had no control over the harvest. This widened the social stratification gap that separated capital owners, the Dutch government, and farmers, and seemed to create shared poverty in society.